Molecular and morphometric analyses reveal discrete grouping of pomegranate (Punica granatum) genebank accessions away from cultivars - ARCHAK, SUNIL; CHANDRA, RAM; GAIKWAD, AMBIKA B; JAMLA, MONICA; PARIMALAN, R; GAUTAM, DIKSHA; JADHAV, V T (The Indian Journal of Agricultural Sciences, 2014)
Management of germplasm in the field genebanks is greatly assisted by genetic analysis. Estimation of genetic diversity and assessment of genetic relationships among 45 accessions of pomegranate (Punica granatum L.) that included cultivars and germplasm collections were carried out using nine morphometric, 241 ISSR and six SSR markers. The average genetic distance values based on ANOVA sum of squares (Ward) were 3.94 and 5.10 for morphometric and DNA markers respectively. Hierarchical clustering based on genetic distances grouped the accessions into at least three distinct clusters; the two-way clustering showing the contribution of individual markers in genetic grouping. Discrete grouping of field genebank accessions (with IC numbers) away from cultivars was evident based both on quantitative traits data as well as DNA marker data. The findings suggested the possibility of broadening genetic base of cultivated varieties by augmenting the breeding programmes in India with diverse as well as trait- specific pomegranate germplasm.